A case of chronic hypomagnesemia in a cancer survivor. Issue 2 (15th March 2017) - Velimirovic, Marko; Ziperstein, Joshua Charles; Fenves, Andrew Zoltan
ABSTRACT: Objectives : Hypomagnesemia is common among hospitalized patients, particularly those who are critically ill. It can be associated with a number of potentially life-threatening cardiovascular, neurological and behavioral manifestations. As opposed to acute, chronic hypomagnesemia is often underdiagnosed and underreported and as such may pose a diagnostic and therapeutic problem. Case presentation : We describe a case of magnesium wasting in a middle-aged woman with head and neck cancer who presented with recurrent syncopal episodes complicated by a femur fracture 4 months after completing a course of carboplatin-containing chemotherapy. Fractional excretion of magnesium of 16% was consistent with renal wasting of magnesium. After ruling out all common causes of hypomagnesemia, it was concluded that she sustained carboplatin-induced renal tubular damage making her relatively resistant to magnesium supplementation. Conclusion : Several antineoplastic agents have been linked to chronic hypomagnesemia including anti-epidermal growth factor receptor agents such as cetuximab and panitumumab, cyclosporine, and the platinum-based agents cisplatin and carboplatin. The example case presented here illustrates the importance of chronic hypomagnesemia and its possible debilitating effects following carboplatin-containing chemotherapy. A growing numbers of cancer survivors are treated with these antineoplastic agents, and are hospitalized for non-cancer-related problems. These patients may have prolonged hypomagnesemia, and hence pose a diagnostic dilemma. We review the pathophysiology, etiology, diagnosis, clinical manifestations, monitoring and treatment of hypomagnesemia, with special attention to mechanisms of renal damage caused by platinum-containing chemotherapeutic agents.